Dim Red Light During Scotophase Enhances Mating of a Moth Through Increased Male Antennal Sensitivity Against the Female Sex Pheromone - Chen, Qiuying; Yang, Xi; You, Dongrui; Luo, Jiaojiao; Hu, Xiaojing; Xu, Zhifeng; Xiao, Wei (Frontiers in Genetics, 2021)
Insects are behaviorally and physiologically affected by different light conditions, including photoperiod, light intensity, and spectrum. Light at night has important influences on nocturnal insects, including most moth species. Moth copulation and mating usually occur at night. Although a few studies examine changes in insect mating under artificial light at night, detailed influences of light, such as that of monochromatic light, on moth mating remain largely unknown. In this study, on the basis of long-term experience rearing insects, dim red light (spectrum range: 610 to 710 nm, with a peak at 660 nm; 2.0 lux) during scotophase was hypothesized to enhance mating in the yellow peach moth, Conogethes punctiferalis. To test the hypothesis, the mating of moths under dim red, blue, and white lights during scotophase was observed. Under the dim red light, the enhancement of mating in C. punctiferalis was observed. In addition, the electroantennografic response of males increased with red light treatment during scotophase. In an analysis of the differentially expressed genes in the antennae of males under red light and dark conditions, the expression levels of two odorant-binding protein genes, CpunOBP2 and CpunPBP5, were up-regulated. Two genes were then expressed in Escherichia coli, and the recombinant proteins showed strong binding to female pheromone components in fluorescence-binding assays. Thus, the results of this study indicated that dim red light at night enhanced the mating of C. punctiferalis. One of the mechanisms for the increase in mating was probably an increase in the antennal sensitivity of males to the female sex pheromone under red light that was caused by increases in the expression levels of pheromone-binding protein genes in male antennae.